The history of beauty pageant in Zimbabwe from 1980 to 2017. - Makuyana, Tafara (Midlands State University, 2020)
The dissertation examine contemporary Zimbabwean ideologies and ideals of female beauty through the beauty pageant phenomenon. The concept of beauty is revealed in the study as many people wildly use beauty as something to deal with outer appearance in today’s world. The study represent all types of beauty pageants including fashion modelling, commercial modelling and advertising. Similar events for men and boys are called by other names and are more likely to bodybuilding. The research illustrate the difficulties to keep up with the number of pageants held say every month as the number continue to increase and explore the dynamism in use of ancient pageant and unravel factors that influence the transformation of beauty pageant. Many beauty pageants over the years have drawn attention for all the wrong reason, the dissertations talks about the types of scandals that have left multiple winners stripped their crowns identifying specific individuals that were directly involved in the scandals and controversies.